2018
DOI: 10.1016/j.celrep.2018.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Directional Reaching for Water as a Cortex-Dependent Behavioral Framework for Mice

Abstract: SummaryOptogenetic tools and imaging methods for recording and manipulating brain activity have boosted the field of neuroscience in unprecedented ways. However, behavioral paradigms for mice lag behind those of primates, limiting the full potential of such tools. Here, we present an innovative behavioral framework in which head-fixed mice directionally reach for water droplets, similar to the primate “center-out” reaching task. Mice rapidly engaged in the task, performed hundreds of trials, and reached in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 73 publications
13
107
0
Order By: Relevance
“…Determining if this pattern is based on sensory feedback mechanisms within a specific trial, or is an overall motor control strategy unrelated to feedback, could inform hypotheses about the neural circuits involved in its control. Mice may have difficulty sensing pellet depth; olfactory cues may be somewhat noisy, visual cues appear unnecessary, and somatosensation is precluded as whiskers are blocked from the target (Galiñanes et al, 2018a;Whishaw & Tomie, 1989). Importantly, we observed multiple attempt reaches in both freely-behaving and head-fixed conditions, pointing to a broader reliance on the multiple-attempt strategy than previously suggested.…”
Section: Regulation Of Motor Variabilitysupporting
confidence: 39%
See 1 more Smart Citation
“…Determining if this pattern is based on sensory feedback mechanisms within a specific trial, or is an overall motor control strategy unrelated to feedback, could inform hypotheses about the neural circuits involved in its control. Mice may have difficulty sensing pellet depth; olfactory cues may be somewhat noisy, visual cues appear unnecessary, and somatosensation is precluded as whiskers are blocked from the target (Galiñanes et al, 2018a;Whishaw & Tomie, 1989). Importantly, we observed multiple attempt reaches in both freely-behaving and head-fixed conditions, pointing to a broader reliance on the multiple-attempt strategy than previously suggested.…”
Section: Regulation Of Motor Variabilitysupporting
confidence: 39%
“…Thus, charting similarities and differences in basic kinematic measurements across behavioral contexts and across species can provide stepping stones for future experiments aimed at uncovering neural mechanisms into how the nervous system produces reach behavior. Although some prior studies quantified aspects of mouse reach kinematics, the majority focused mainly on success rates, qualitative descriptions and scoring systems, or categorical demarcation of the reach into phases, with few explicit connections drawn to the kinematic control principles discussed here (Esposito et al, 2014;Farr & Whishaw, 2002;Galiñanes et al, 2018b;Guo et al, 2015;Whishaw, 1996;Whishaw et al, 2017Whishaw et al, , 2018Whishaw & Pellis, 1990). This study establishes several basic quantitative frameworks for analyzing mouse reach kinematics, allowing numerical comparisons to be drawn across species and across tasks.…”
Section: Comparative Kinematics Support Reach Homology Across Speciesmentioning
confidence: 91%
“…encompassing cerebellum and cortex, or cerebellum and rostral striatum) in freely behaving animals opens up new avenues for research into cerebello-cerebral and cerebello-striatal interactions during the expression of innate and learned behaviors and can help to resolve outstanding questions with regard to the role of the cortical and subcortical structures in planning, learning and executing skilled movements (Guo et al 2015;Kawai et al 2015;Sauerbrei et al 2018;Gao et al 2018) . Changes in joint cell participation during procedural learning (Galiñanes, Bonardi, and Huber 2018;Guo et al 2015) can be quantified concurrently in cortical and subcortical structures to determine if cell responses are enhanced or suppressed (Kostadinov et al 2019) . Although we did not find a consistent spatial clustering of activity in cerebellum and cortex when neurons in both regions displayed joint activity, a more careful parcellation of the motor behavior in a larger sample may reveal that such clustering does indeed occur.…”
Section: Cerebello-cerebral Interactionsmentioning
confidence: 99%
“…Often an anatomical substrate exists for clustered activity such as is the case in the cerebellum, where nearby Purkinje cells receive input from climbing fibers originating in adjacent neurons of the inferior olive brainstem nucleus (Ruigrok 2010) . Thus, imaging approaches can reveal how individual cells embedded in a larger network display coordinated activity during different stages of behavior or training (Wagner et al 2017;Heffley et al 2018;Galiñanes, Bonardi, and Huber 2018;Giovannucci et al 2017) . Moreover, because of their ability to record in freely moving animals, miniscopes have been instrumental in uncovering neural activity patterns occurring during natural behaviors and related brain-states including social interactions (Murugan et al 2017;Remedios et al 2017;Liang et al 2018;Kingsbury et al 2019) or sleep Cox, Pinto, and Dan 2016) with fully intact vestibular input.…”
Section: Introductionmentioning
confidence: 99%
“…In nonhuman primates, motor cortical lesions impair the coordination of the hand and fingers (3), and the activity of motor cortical neurons is closely linked to muscle activation, joint torques, and limb kinematics (4,8,10). In rodents, stimulation of motor cortex generates limb twitches (12,13), chronic lesions impair dexterity (14,15), and optogenetic inactivation blocks the initiation and execution of reaching (16,17). However, several studies have concluded that motor cortex may play a fundamentally different role in rodents than in primates (18), such as tutoring other brain regions during learning (19,20) or suppressing actions (21).…”
Section: Introductionmentioning
confidence: 99%